2003
DOI: 10.1038/sj.onc.1206164
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of uPA inhibits migration and PI3k/Akt signaling in glioblastoma cells

Abstract: The ability of glioma cells to migrate great distances from a primary tumor mass is the primary cause of tumor recurrence. The urokinase-type plasminogen activator (uPA) is a serine protease that can initiate proteolytic cascades, which result in remodeling of extracellular matrix and basement membrane, allowing cells to move across and through these barriers. The binding between uPA and its receptor uPAR also mediates several signaling events that seem to contribute to the evolution of a migratory phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 46 publications
(43 reference statements)
3
81
0
Order By: Relevance
“…These Rho-like G-proteins are known principally for their pivotal role in regulating the actin cytoskeleton in cell migration (Burridge and Wennerberg, 2004). PI3K has been thought to be a key molecule in the activation of cell migration through Rac signaling (Chandrasekar et al, 2003;van Leeuwen et al, 2003 Kawauchi et al, 2003) and p38MAPK (Rousseau et al, 1997;Cara et al, 2001;Ishizuka et al, 2001;Kimura et al, 2003;Pichon et al, 2004), have also been reported to be involved in cell migration. Consistent with these reports, our results indicate that activation of PI3K is required for the induction of glioma cell migration as well as for the activation of p38MAPK and JNK in response to LPA.…”
Section: Discussionmentioning
confidence: 99%
“…These Rho-like G-proteins are known principally for their pivotal role in regulating the actin cytoskeleton in cell migration (Burridge and Wennerberg, 2004). PI3K has been thought to be a key molecule in the activation of cell migration through Rac signaling (Chandrasekar et al, 2003;van Leeuwen et al, 2003 Kawauchi et al, 2003) and p38MAPK (Rousseau et al, 1997;Cara et al, 2001;Ishizuka et al, 2001;Kimura et al, 2003;Pichon et al, 2004), have also been reported to be involved in cell migration. Consistent with these reports, our results indicate that activation of PI3K is required for the induction of glioma cell migration as well as for the activation of p38MAPK and JNK in response to LPA.…”
Section: Discussionmentioning
confidence: 99%
“…Urokinase itself has been reported to stimulate PI3K activity and activates the downstream effectors Akt [15,16] and Rac1 [17]. Inversely, antisense uPA in glioblastoma cells causes a decrease both in wound migration and in PI3K/Akt activity [18]. Conversely, looking at PAI-1 levels, both hypoxia-induced PAI-1 expression [19] and nerve growth factor-induced PAI-1 expression [20] can be inhibited by PI3K inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Selected cells were lysed in RIPA buffer (50 mM Tris at pH 8, 150 mM NaCl, 1% NP40, 0.5% deoxycholate, 0.1% SDS). 20, 40 or 80 micrograms of Proteins (20,40 or 80 Âľg) were separated by 8-12% SDS-PAGE and transferred to polyvinylidine difluoride membranes (Millipore, Billerica, MA). Western blots were probed with the indicated antibodies.…”
Section: P53mentioning
confidence: 99%
“…Therefore, mitogenic signalling through PI(3)K-PKB-GSK3β influences cyclin D1 stability and its nuclear activity, leading to cell-cycle progression 2 . uPA induces growth factor-related PI(3)K-PKB signalling 20 and, as a result, uPA activity may result in nuclear retention of cyclin D1 by inducing loss of GSK3β activity through phosphorylation on Ser 9. When cyclin D1 localization was determined in ageing MEFs, a striking but gradual nuclear exclusion of cyclin D1 was observed (Fig.…”
mentioning
confidence: 99%